COMMON BACTERIOLOGICAL PATHOGENS AND THEIR ANTIBIOTIC SENSITIVITY PATTERN IN BILE OF PATIENTS WITH CHOLELITHIASIS - Hameed, Kanwal; Amir Ali, Asif Ali; Parveen, Sughra; Khan, Imran; Ali, Jehangir; Waheed, Abdul (Infectious Diseases Journal of Pakistan, 2023)
Background: To determine the pattern of antibiotic susceptibility of common bacteriological pathogens of bile in patients with Cholelithiasis. Material and Methods: A prospective cross-sectional study was conducted in the department of surgery, Jinnah Postgraduate Medical Center, from January 2020 to July 2020. All patients between the ages of 16 and 65, with symptomatic cholelithiasis operated by open or laparoscopic cholecystectomy were included in this study. Patients with acute cholecystitis, obstructive jaundice, and common bile duct stones were excluded from the study. Cultures and Sensitivity tests were performed for aerobes and anaerobes pathogens in JPMC laboratory. Socio-demographic variables and clinical parameters were recorded in a predefined proforma. Data was entered and analyzed using Statistical Package for Social Sciences version 26. Results: Out of a total of 610 samples, 314 cultures were positive for bacteria. Bacteriological investigation revealed Escherichia coli was isolated in 97 (30.89%) patients, Escherichia coli and Klebsiella pneumoniae in 66 (21.02%), Escherichia coli, Klebsiella pneumoniae, and Shigella sonnei in 18 (5.73%), Escherichia coli, Salmonella enterica in 18 (5.73%), only Klebsiella pneumoniae in 64 (20.38%), Salmonella enterica in 15 (4.78%), Salmonella enterica and Klebsiella pneumoniae in 32 (10.19%), and Shigella sonnei in 4 (1.27%) patients. The most susceptible antibiotic for microorganisms on the whole was Imipenem (66.7%). The highest resistance was shown against Cefradine (76.4%). Conclusion: The current study concludes that the most common bacteria of symptomatic cholelithiasis are Escherichia coli and Klebsiella pneumoniae followed by Salmonella enterica and Shigella sonnei. These bacteria showed an overall susceptibility to Imipenem. Key Words: Bacteriological investigation, Symptomatic cholelithiasis, Culture, Sensitivity, Antibiotics